1999
DOI: 10.1002/j.2161-1874.1999.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Resources on Job Stress Among Correctional Treatment Staff

Abstract: In an exploratory study of the relationship between resources in the work environment and job stress, correctional treatment staff members reporting quality personal relationships in the work environment also experienced fewer stressors at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
15
0
4
Order By: Relevance
“…One way of understanding this broader literature is to consider the social climate of an organisation as a job resource. According to and Waters (1999) a job resource has the capacity to mitigate the effects of stress that is generated by job demands. , for example, reported that social climate moderated the relationship between negative pupil behaviour and work engagement amongst teachers.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
“…One way of understanding this broader literature is to consider the social climate of an organisation as a job resource. According to and Waters (1999) a job resource has the capacity to mitigate the effects of stress that is generated by job demands. , for example, reported that social climate moderated the relationship between negative pupil behaviour and work engagement amongst teachers.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
“…Waters (1999) found that treatment staff viewed their supervisors favorably in a number of ways. A good majority of the treatment staff reported that their supervisors gave compliments when appropriate, discussed personal problems, and stood up for employees.…”
Section: Perceptions and Predictors Of Management In Prisonsmentioning
confidence: 99%
“…Supervisory support refers to support from direct supervisors of employees, while managerial support refers to support from higher ups, perhaps those the worker rarely sees. Both supervisors and management play vital roles in the work lives of employees (Garland & McCarty, 2006;Walters, 1999). Supervisory support deals with the perception of the degree of support provided to employees by their supervisors (Cullen et al, 1985;House & Dessler, 1974).…”
Section: Literature Reviewmentioning
confidence: 99%